마이크로파 정제에 의한 액정방사용 단일벽 탄소나노튜브의 제조 및 특성 - 김민지; Min Ji Kim; 이동주; Dongju Lee; 구본철; Bon-cheol Ku; 유기현; Ki-hyun Ryu; 김대윤; Dae-yoon Kim; 김남동; Nam Dong Kim (한국섬유공학회지, 2021)
Carbon nanotube fibers (CNTFs) have attracted wide attention owing to their exceptional lightness, electrical conductivity, and mechanical flexibility that make them potential components for applications including carbon composites, nanoelectronics, and optics. CNTFs have been successfully fabricated from carbon nanotubes (CNTs) by liquidcrystal spinning. This spinning method requires low-defect CNTs to form a liquid crystalline phase for making highly-oriented CNTFs. In this study, we conducted microwave purification to effectively remove impurities from CNTs, such as residual metallic catalyst and carbon- based impurities, that are formed during CNT synthesis. We fabricated single-walled carbon nanotube fibers (SWCNTFs) using liquid-crystal spinning purified single-walled carbon nanotubes (SWCNTs) to examine the effect of SWCNTs on the liquid crystal phase and resultant fibers. In conclusion, this method removed impurities from SWCNTs and increased the oxygen-containing functional groups in the SWCNTs, which are capable of forming a liquid crystal phase, thereby enhancing the mechanical performance of fibers.